Fibroblasts From Idiopathic Pulmonary Fibrosis Induce Apoptosis and Reduce the Migration Capacity of T Lymphocytes - Chavez-Galan, Leslie; Becerril, Carina; Ruiz, Andy; Ramon-Luing, Lucero A.; Cisneros, José; Montaño, Martha; Salgado, Alfonso; Ramos, Carlos; Buendía-Roldán, Ivette; Pardo, Annie; Selman, Moisés (Frontiers in Immunology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a progressive and irreversible lung disease of unknown etiology. Myofibroblasts are organized in peculiar sub-epithelial fibroblasts foci (FF), where they abnormally persist and exclude lymphocytes by unclear mechanisms. FF are the source of excessive extracellular matrix, which result in progressive stiffening and destruction of the lung architecture. We hypothesized that the absence of T-cells inside the FF could be related, at least partially, to an inefficient function of lymphocytes induced by IPF fibroblasts. Here, we evaluated the effect of the supernatant from IPF fibroblasts on T-cell apoptosis and migration capacity. Data showed that IPF fibroblasts secrete pro-apoptotic molecules (both, from extrinsic and intrinsic pathways), generating a microenvironment that induces apoptosis of T-cells at 3 h of culture, despite a weak anti-apoptotic profile exhibited by these T cells. At 24 h of culture, supernatants from both, IPF and control fibroblasts, provoked T-cell death. However, at this time of culture, IPF fibroblasts caused a marked decrease in T-cell migration while in contrast, control lung fibroblasts induced an increase of T-cell migration. The reduction of T-cell migratory capacity provoked by IPF fibroblasts was associated with a negative regulation of RHOA and ROCK, two essential GTPases for migration, and was independent of the expression of chemokines receptors. In conclusion, our findings demonstrate that IPF fibroblasts/myofibroblasts induce apoptosis and affect T-cells' migration, revealing a mechanism involved in the virtual absence of T-lymphocytes inside the FF.